Superiority of chlorhexidine 2%/alcohol 70% wipes in decontaminating ultrasound equipment. (August 2014) - Shukla, Bhavin; Howell, Victoria; Griffiths, Alicia; Thoppil, Anita; Liu, Monica; Carter, Joseph; Young, Peter
Ultrasound equipment is known to act as a reservoir for potentially pathogenic organisms. The aims of these studies were to establish current cleaning practices, to review the extent of bacterial contamination of ultrasound equipment in our hospital, to establish an effective cleaning regimen and to ensure that cleaning does not cause damage. A questionnaire was sent to all acute NHS hospitals in England to establish current cleaning practices. A review of our current practice was performed to establish the extent of bacterial contamination of ultrasound equipment currently in use. Laboratory studies compared cleaning the probes with soap and water with decontaminating with a chlorhexidine 2% and alcohol 70% wipe, including quantifying the residual effect. Accelerated aging was performed on the probe and staff surveyed to establish potential problems with using the wipes on the probe. The survey revealed that a variety of cleaning methods were used to decontaminate ultrasound probes; 57% of our ultrasound machines were contaminated with bacteria. The laboratory studies showed superiority of the chlorhexidine and alcohol wipes over soap and water due to a residual effect, both immediately after cleaning and after 24 hours. The staff survey demonstrated no apparent change in function of the probe after cleaning with the chlorhexidine wipes. Cleaning ultrasound probes with chlorhexidine and alcohol wipes is effective and provides additional protection against bacterial contamination due to its residual effect, and appears in the short term to have no detrimental effect on the probe.